Surgical Treatment of Hallux Valgus - Kılıç, B., Çatıkkaş, F., Zekioğlu, A., Yücel, A. S., (My University, 2014)
Hallux valgus deformity is an often deformity in which first metatarsophalangeal joint is subluxated due to the lateral deviation of thumb and medial deviation of metatarsal bone. As deformity progresses, it results in function and uniformity loss, with lateral displacement of thumb and deformity of claw toe and hammer toe. Shoes’ pressure on bunion area causes its inflammation and pain. Conservative and surgical treatment methods are used for the treatment of Hallux valgus deformity. According to the results of our study, which we obtained through soft tissue corrective procedures and bunionectomy applied under local anesthesia to 86 patients with Hallux valgus at different times, patients could walk within a short period of time, wear shoes comfortably, and their pains decreased considerably.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: Hallux Valgus; Chevron Osteotomy; Deformity.